Acute discogenic lumbosacral radiculopathy - V. A. Parfenov (Медицинский совет, 2020)
Discogenic lumbosacral radiculopathy (DLSR) accounts for up to 5% of all cases of pain in the lumbosacral region, representing one of the most common causes of disability in the population. The issues of pathogenesis, risk factors, course, diagnosis, treatment and prevention of DLSR are discussed. It is noted that in the pathogenesis of DLSR, in addition to compression-ischemic lesions of the spinal root, an important role is played by local inflammatory and autoimmune reactions, which underlie the natural decrease in disc herniation over time. The diagnosis of DLSR is established on the basis of signs of damage to the lumbar and first sacral roots and the absence of signs that are alarming regarding the specific causes of back pain. Magnetic resonance imaging (MRI) of the lumbosacral region allows you to exclude specific causes, identify a herniated disc, but its implementation does not improve the prognosis of the disease if there are no signs of a specific disease. Of great importance is informing the patient with acute DLSR about the favorable course of the disease, the possibility of natural (without surgical intervention) regression of the herniated disc and the associated inflammatory changes. Non-drug (therapeutic gymnastics, manual therapy) and drugs (nonsteroidal anti-inflammatory drugs (NSAIDs), antiepileptic drugs, epidural administration of corticosteroids) in acute DLSR are analyzed. Own experience of management of patients with acute DLSR using meloxicam as an NSAID is presented. It is noted that in the prevention of low back pain, the avoidance of excessive physical and static stress, regular exercises in therapeutic gymnastics, swimming, walking are of leading importance.